2013
DOI: 10.1007/s10508-013-0181-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Sexual Desire Discrepancy Among Married Couples

Abstract: Previous studies have found associations between the individual discrepancy of desired sexual frequency and actual sexual frequency and relational outcomes among premarital couples. The present study extended this research by using a sample of 1,054 married couples to explore how actor and partner individual sexual desire discrepancy (SDD) scores were associated with relationship satisfaction, stability, communication, and conflict during marriage. All participants took an online survey which assessed both cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 35 publications
0
26
0
1
Order By: Relevance
“…Sexual satisfaction is positively associated with marital quality, and high levels of marital quality, in turn, predict marital stability (Yeh et al, 2006). Conversely, sexual dissatisfaction contributes to marital instability; discrepancies between one's desire for sex and reported frequency of sex with one's spouse predict lower levels of relationship satisfaction and perceptions of stability as well as higher levels of marital conflict and disruption (Brezsnyak & Whisman, 2004;Dzara, 2010;Willoughby, Farero, & Busby, 2014). Although frequency of sex tends to decline with age, Lindau et al (2007) report that the majority of adults aged 57 to 74 believe that sexuality is an important part of life.…”
Section: Sex Marriage and Midlife Seen Through A Gender-as-relationmentioning
confidence: 99%
“…Sexual satisfaction is positively associated with marital quality, and high levels of marital quality, in turn, predict marital stability (Yeh et al, 2006). Conversely, sexual dissatisfaction contributes to marital instability; discrepancies between one's desire for sex and reported frequency of sex with one's spouse predict lower levels of relationship satisfaction and perceptions of stability as well as higher levels of marital conflict and disruption (Brezsnyak & Whisman, 2004;Dzara, 2010;Willoughby, Farero, & Busby, 2014). Although frequency of sex tends to decline with age, Lindau et al (2007) report that the majority of adults aged 57 to 74 believe that sexuality is an important part of life.…”
Section: Sex Marriage and Midlife Seen Through A Gender-as-relationmentioning
confidence: 99%
“…A combined score still captures the overall influence but does not produce problematic results by introducing necessary variance between the discrepancy score and the combined score. While this does not allow for the specific investigation of male or female pornography use independently predicting couple-level outcomes, it does increase the confidence that difference scores are producing significant results independent of baseline measurements.Previousstudieshaveutilizedasimilarstrategytoexamine if discrepancy scores have unique contributions once baseline assessments are controlled for (Busby, Holman, & Neihuis, 2009;Willoughby, Farero, & Busby, 2014). Once computed, scores on total use ranged from 0 to 9 (M = 1.95, SD = 1.74).…”
Section: Couple Sexualitymentioning
confidence: 99%
“…A similar investigation found that individual discrepancy between sexual desire and sexual frequency was associated with negative marital outcomes [10]. However, this discrepancy was also shown to lead to positive outcomes if the relationship in question was in the earliest stages, possibly because it provided motivation to put more effort into supporting the relationship.…”
Section: Psychological Loss Of Sexual Desirementioning
confidence: 94%